Motivational Values of Education in the Hadiths about Seeking Knowledge from the Perspective of Islamic Education - Lutfiyah Agnung Anggraeni; Mohammad Fattah (Penerbit Presisi Pustaka, 2026)
The hadiths of the Prophet Muhammad (peace be upon him) about seeking knowledge contain fundamental educational motivational values ​​from an Islamic educational perspective. This study aims to examine and analyze the educational motivational values ​​contained in the hadiths about seeking knowledge and their relevance in the context of contemporary Islamic education. This study uses a qualitative approach with descriptive-analytical library research. The research data were obtained from thematic hadith literature, Islamic education books, and scientific journal articles relevant to the theme of educational motivation. The results show that the hadiths about seeking knowledge contain intrinsic motivational values ​​in the form of sincerity of intention, awareness of the obligation to seek knowledge, and an orientation towards worship in the learning process, as well as extrinsic motivational values ​​in the form of the promise of reward, the noble status of those who are knowledgeable, and the ease of the path to heaven. These motivational values ​​have strong relevance in facing the pragmatic and materialistic tendencies of contemporary education. The integration of hadith-based educational motivational values ​​is expected to strengthen the holistic, sustainable orientation of Islamic education (lifelong learning), and oriented towards the formation of knowledgeable, faithful, and noble individuals.